Microbiota alteration of Chinese young male adults with high-status negative cognitive processing bias - Xu, Hui-Min; Xie, Shen-Wei; Liu, Tian-Yao; Zhou, Xia; Feng, Zheng-Zhi; He, Xie (Frontiers in Microbiology, 2023)
ABSTRACT Evidence suggested negative cognitive processing bias (NCPB) is a crucial and risk factor of depression. Microbiota-gut-brain axis, have been proved to be a contributing factor for cognitive health and disease. However, the connection between microbiota and NCPB remains unknown. This study mainly sought to explore the key microbiota involved in NCPB and the possible pathways through which NCPB affects depressive symptoms. Data in our studies was collected from 735 Chinese young adults through a cross-sectional survey. Fecal samples were collected from 35 young adults with different level of NCPB (18 individuals were recruited as high-status NCPB group.And another 17 individuals were matched as low-status NCPB group) and 60 with different degree of depressive symptoms (27 individuals were recruited into depressive symptoms group, as D group. And 33 individuals were matched into control group, as C group), and analyzed by the 16S ribosomal RNA sequencing technique. As a result, the level of NCPB correlated with the degree of depressive symptoms as well as anxious symptoms and sleep quality (p<0.01). The β-diversity of microbiota in young adults were proved to be significantly different between the high-status of NCPB and the low-status of NCPB groups. There were several significant increased bacteria taxa, including Dorea, Christensenellaceae, Christensenellaceae_R_7_group, Ruminococcaceae_NK4-A214_group, Eggerthellaceae, Family-XIII, Family_XIII_AD3011_group, Faecalibaculum and Oscillibacter. They were mainly invovled in pathways included short-chain fatty acids (SCFAs) metabolism. Among these variable bacteria taxa, Faecalibaculum were found associated with both NCPB and depressive symptoms. Furthermore, 5 pathways related to SCFAs metabolism turned out to be significantly alter in both the high-status NCPB group and the depressive symptoms group, including butanoate metabolism, glyoxylate and dicarboxylate metabolism, propanoate metabolism, phenylalanine, tyrosine and tryptophan biosynthesis, valine, leucine and isoleucine degradation. In conclusion, Fecal microbiota is altered in Chinese young male adults with high-status of NCPB and may be involved in the biochemical progress influences depressive symptoms.